Self-reported physical inactivity and health complaints: a cross-sectional study of Lithuanian adolescent schoolgirls - Romualdas Malinauskas; Vilija Malinauskaiene (Cadernos de Saúde Pública, 2015)
The study aimed to investigate the associations between physical inactivity and health complaints in relation to posttraumatic stress (PTS) symptoms, behavioral and nutritional factors, and sense of coherence (SOC) in eighth-grade girls enrolled in secondary schools in Kaunas, Lithuania. A random sample of girls (N = 862) was interviewed anonymously on health complaints, physical activity level, PTS symptoms, Antonovsky’s SOC scale, health behaviors, and dietary patterns. All health complaints were significantly associated with physical inactivity. Crude odds ratio (OR) for physical inactivity and health complaints was 1.67 (95%CI: 1.09-2.56); after adjusting for PTS symptoms, the OR decreased to 1.57 (95%CI: 0.95-2.45); further adjustment for smoking, daily alcohol intake, daily consumption of fresh vegetables, and SOC decreased the OR to 1.25 (95%CI: 0.76-2.04). The effect of PTS symptoms and sense of coherence remained stable after all adjustments. The significant association between physical inactivity and health complaints was mediated by PTS symptoms.